Sintered engine part and method of manufacturing the same

By using a mixture of two iron-based powders and copper diffusion and penetration technology during sintering, the problems of wear resistance and retention ability of the powder metallurgy valve seat insert at high temperatures are solved, and efficient material performance improvement is achieved.

CN120115685APending Publication Date: 2025-06-10L E JONES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795999.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-08
Filing Date
2024-12-09
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

Powder metallurgy valve seat insert materials have challenges in wear resistance, thermal shock resistance, fatigue crack resistance, corrosion resistance and insert retention ability, especially the problem of copper penetration increasing the tendency of adhesion wear at high temperatures.

Method used

A mixture of two iron-based powders is used, including a high hardness first iron-based powder and a second iron-based powder of vanadium-free tool steel, which contains vanadium carbide particles to reduce adhesion wear and fill gaps through copper diffusion and permeation of copper during sintering to improve bond strength and density.

Benefits of technology

It realizes the wear resistance and crack resistance of the valve seat insert at high temperatures, reduces adhesion wear, enhances the material retention ability and density distribution, and reduces process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120115685A_ABST
    Figure CN120115685A_ABST
Patent Text Reader

Abstract

A powder mixture for manufacturing sintered engine parts, such as valve seat inserts, comprising a first iron-based powder and a second iron-based powder wherein the first iron-based powder has a higher hardness than the second iron-based powder, the first iron-based powder comprising, in weight percent, 1-2% C, 10-25% Cr, 5-20% Mo, 15-25% Co, and 30-60% Fe; the second iron-based powder comprises a vanadium-free tool steel powder, such as a vanadium-free tool steel, comprising, in weight percent, 1-1.5% C, 3-15% Cr, 5-7% Mo, 3-6% W and 60-85% Fe; the second iron-based powder further includes vanadium carbide particles in an amount sufficient to reduce adhesive wear. The powder mixture may be sintered to form a sintered engine part optionally infiltrated with copper.
Need to check novelty before this filing date? Find Prior Art

Description

BACKGROUND OF THE INVENTION

[0001] Powder metallurgy (PM) valve seat insert (VSI) materials continue to face significant challenges for medium - to - heavy - duty internal combustion (IC) engine VSI applications in terms of wear resistance, thermal shock resistance, fatigue crack resistance, corrosion resistance, and insert retention ability. Iron - based sintered valve seat inserts typically add intermetallic compounds and / or silicide hard particles. Achieving a uniform distribution of such hard particles can be difficult, and due to the presence of these hard particles, the performance of the final product may not be optimal. For example, two commercial PM VSI materials, AP - grade and S - grade PM materials, include hard particles such as tribaloy powder and VCN. One of them is made by a double - press and double - sinter (2P2S) process, while the other is made by a single - sinter plus copper infiltration process; the one made by the 2P2S process is significantly superior to the one made by the sinter plus copper infiltration process in multiple engine tests.

[0002] When the VSI operating temperature is not very high, copper infiltration can fill PM pores, thus improving wear resistance. Compared with common iron - based, nickel - based, or cobalt - based alloys, copper / copper alloys have a low melting temperature, low strength, and a high affinity for many other metals / alloys. Therefore, at high temperatures, a large amount of copper infiltration will increase the tendency of adhesive wear and may reduce the performance of PM VSI materials. For the same reason, compared with massive copper formed by gravity copper filling in parts, infiltrated copper formed by capillary reaction in thin corrugated plates can effectively improve wear resistance.

[0003] Modern internal combustion engine designs must consider high - temperature and high - pressure environments. Copper - infiltrated VSIs will increase the heat transfer rate, taking the exhaust gas heat from the valve to the engine pocket, thus reducing the temperature gradient in the radial orientation of the VSI. Therefore, for copper - infiltrated VSIs, the highest temperature of the contact surface between the VSI OD and the pocket is higher than that of non - copper - infiltrated VSIs. Therefore, compared with the non - copper - infiltrated version, a VSI with copper infiltration may have a lower retention ability, making it more sensitive to insert dropout. The effect of copper infiltration on the part retention ability is related to the morphology and content of copper in the PM VSI.

[0004] The most widely used PM bonding mechanism is diffusion bonding through the sintering process. The sintering process affects the bonding strength between adjacent powders in PM materials and thus has a significant impact on the wear resistance of the materials. Double - press and double - sinter (2P2S) can increase density and powder bonding strength. However, 2P2S will not be able to change the uniformity of powder distribution and has the obvious disadvantage of a higher process cost. Therefore, an ideal bonding strength concept is needed, which should start from powder mixture design, compaction conditions, and sufficient sintering parameters. SUMMARY OF THE INVENTION

[0005] In one embodiment, a powder mixture useful for manufacturing sintered engine parts includes a first iron-based powder and a second iron-based powder, wherein the first iron-based powder has a higher hardness than the second iron-based powder. The first iron-based powder includes, in weight percentage (wt.%), 1-2% C, 10-25% Cr, 5-20% Mo, 15-25% Co, and 30-60 wt.% Fe, and the second iron-based powder includes a vanadium-free tool steel, wherein the second iron-based powder further includes vanadium carbide particles present in an amount sufficient to reduce adhesive wear.

[0006] Depending on various options, (a) the first iron-based powder has a microstructure with interdendritic and intra-dendritic solidification substructures, with up to 25% sigma phase; (b) the powder mixture further includes up to 20% Fe powder; (c) the powder mixture includes up to 3% Cu powder; (d) the powder mixture includes up to 2% MnS powder; (e) the powder mixture includes up to 2% die lubricant; (f) the first iron-based powder comprises, consists essentially of, or consists of: 1-2% C, 10-25% Cr, 5-20% Mo, 15-25% Co, up to 1% Mn, up to 1% Si, up to 5% Ni, up to 5% W, up to 2% V, up to 0.5% B, up to 0.1% P, up to 0.1% S, up to 0.5% N, up to 0.5% Nb, with the balance being 30-60% Fe and incidental impurities; (g) the second iron-based powder comprises, consists essentially of, or consists of: by weight %, 1-1.5% C, 3-15% Cr, 5-7% Mo, 3-6% W, up to 1% Mn, up to 1% Si, with the balance being 60-85% Fe and incidental impurities, and optionally free of Ni, optionally free of Co, and optionally free of Nb; (h) the first iron-based powder is present in an amount of 40-60 wt.%, and the second iron-based powder is present in an amount of 20-40 wt.%; (i) the powder mixture includes Fe powder, Cu powder, and MnS powder, the first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, Fe powder is present in an amount of 15-20 wt.%, Cu powder is present in an amount of 1-3%, and MnS powder is present in an amount of 0.1-1 wt.%; (j) the powder mixture is free of added silicide, molybdenum-based, cobalt-based, and intermetallic hard particle powders; (k) the first iron-based powder has a microstructure consisting of 40-60 vol.% interdendritic regions and 60-40 vol.% intra-dendritic regions; (l) except for vanadium carbide particles, the powder mixture is free of other hard particle powders with a hardness greater than that of the first iron-based powder; (m) the vanadium carbide particles have an average particle size of 1-150 microns; (n) the vanadium carbide particles are vanadium carbonitride particles with an average size of 1-150 microns; and / or (o) the vanadium carbide particles are present in an amount of 0.5-1.5 wt.%.

[0007] The powder mixture can be used to manufacture sintered engine parts, such as valve seat inserts, where the powder mixture has been compacted into the shape of the engine part, sintered to form a sintered powder mixture, and optionally infiltrated with copper.

[0008] Depending on various options, (a) the sintered powder mixture has a density of at least 7.5 g / cm 3The density; (b) The first iron-based powder has a microstructure composed of 40-60 vol.% interdendritic regions and 60-40 vol.% intradendritic regions; (c) Except for vanadium carbide particles, the sintering mixture does not contain hard particles with a hardness greater than that of the first iron-based powder; (d) The sintering mixture does not contain added silicides, Mo-based, Co-based, or intermetallic hard particle powders; (e) The first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, and the Fe powder is present in an amount of 15-20 wt.%; and / or (f) The first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, the Fe powder is present in an amount of 15-20 wt.% and copper is present in an amount of 10-15 wt.%.

[0009] A method of manufacturing a sintered engine part may include forming a mixture by mixing a first iron-based powder with a second iron-based powder, compacting the mixture, and sintering the mixture.

[0010] According to various options, (a) Sintering includes preheating the powder mixture at 560 °C, 850 °C, and 950 °C for 5-20 minutes, and then sintering at 1120 °C for 40-60 minutes; (b) Sintering includes a double pressing and double sintering process; (c) Cryogenic treatment of the sintered part in liquid nitrogen; (d) Steam treatment of the sintered part; and / or (e) Sintering while infiltrating the mixture with copper. Description of the Drawings

[0011] Figure 1 is a graph of the compressive yield strength versus temperature, Figure 2 is a graph of the ultimate tensile fracture strength of the sintered part versus temperature. Detailed Description

[0012] Disclosed herein is a powder metal material (referred to herein as "JP513VC") that eliminates the need for hard intermetallic compounds / silicide hard particles by using a mixture of two iron-based powders. JP513VC includes two iron-based powders that can be pressed and sintered to form engine parts such as valve seat inserts or other parts suitable for medium- to heavy-duty engine applications.

[0013] One of the key factors affecting PM VSI performance is the compact density. Performance issues related to the wear resistance, crack resistance, and retention ability of PM VSI can be traced back to the compact density / density distribution related to the powder mixing process, powder shape, powder uniformity, and size distribution. Therefore, it is desirable to achieve good density and the desired density distribution in the design and manufacture of heavy-duty PM materials.

[0014] When the working temperature of VSI is not very high, copper infiltration can fill the PM pores, thus improving wear resistance. Copper and copper alloys generally have relatively low melting temperatures, low strength, and high affinity for many other metals / alloys. Therefore, this kind of copper or copper alloy will affect the tendency of adhesive wear and have a significant impact on the properties of PM VSI materials. For the same reason, compared with the massive copper formed by gravity copper filling in parts, the infiltrated copper formed by capillary reaction in the formation of thin corrugated plates can effectively improve wear resistance.

[0015] Modern internal combustion engine design needs to consider high working temperatures and pressures. Copper-infiltrated VSI will increase the heat transfer rate, taking the exhaust heat from the valve to the engine pocket, thus reducing the temperature gradient in the radial orientation of VSI. Therefore, for copper-infiltrated VSI, the maximum temperature on the contact surface between VSI OD and the engine cylinder head pocket is higher than that of the non-copper-infiltrated version of the engine. Therefore, the retention ability of VSI with copper infiltration may be lower than that of the non-copper-infiltrated version and is more sensitive to insert dropout. The effect of copper infiltration on the part retention ability is related to the morphology and content of copper in PM VSI.

[0016] The most widely used PM bonding mechanism is diffusion bonding through the sintering process. The sintering process affects the bonding strength between adjacent powders in PM materials and thus has a significant impact on the wear resistance of the materials. Double pressing and double sintering (2P2S) can increase density and powder bonding strength. However, 2P2S will not be able to change the uniformity of powder distribution and at the same time has the obvious disadvantage of higher process costs. Therefore, the ideal bonding strength should start from powder mixture design, compaction conditions, and sufficient sintering parameters.

[0017] Additive copper powder can be used to generate transient liquid phase formation during the sintering process to diffuse into iron and iron-based powders in the initial stage of the sintering process. The melting point of copper is 1083 °C, which is lower than the typical sintering temperature (e.g., 1120 °C). During the initial sintering process, the iron-based powders have a high solubility of copper. The degree and amount of copper diffusion into the iron-based powders are related to the sintering temperature and duration. The diffusion of copper into the iron-based powders can help the bonding between the iron-based powders and other additive powders, that is, additive copper can effectively help the formation of bonding between the iron-based powders and other additive powders through the transient liquid phase sintering process. In addition, the iron-based powders containing diffused copper enhance the hardenability of the sintered material. When the copper diffusion process stops, any remaining copper liquid can fill the gaps formed between the compacted powders through a process that minimizes the interfacial free enthalpy thermodynamically. Compared with the effect of infiltrated copper, combined with appropriately designed dense density and density distribution, the method of mixed copper powder can reduce the number of PM pores and form a stronger bond.

[0018] In JP513VC, up to 20 wt.% (e.g., 15 - 20 wt.%, 16 - 19 wt.%, 17 - 18 wt.%) of pure iron powder can be included as the binder powder, where the solubility of copper is up to 10 wt.%. Copper can diffuse into the iron powder, thereby increasing the strength of the pure iron powder to minimize the strength variation between the powder and the powder boundary.

[0019] For iron-based powder materials used in VSI non-copper infiltration applications, steam treatment can be a very cost-effective process. Like the copper infiltration process, the optimal effect of the steam treatment process on PM VSI materials is directly related to the PM apparent density, especially the PM porosity size, shape, and distribution. The iron oxide formed during the steam treatment process is beneficial for improving the PM wear performance. However, the formation of a large amount of iron oxide will reduce the bond formed between powder particles.

[0020] The JP513VC powder mixture can include 40 - 60 wt.% (e.g., 45 - 55 wt.%, 48 - 52 wt.%, 50 wt.%) of a first iron-based powder and 20 - 40 wt.% (such as 25 - 35 wt.%, 28 - 32 wt.%, 30 wt.%) of a second iron-based powder. These two iron-based powders can have the same particle size range but different compositions. The first iron-based powder can include, by weight (wt.%) 1 - 2% C, 10 - 25% Cr, 5 - 20% Mo, 15 - 25% Co, and 30 - 60% Fe, while the second iron-based powder can contain vanadium carbide particles and vanadium-free tool steel, which contains 1 - 1.5% C, 3 - 15% Cr, 5 - 7% Mo, 3 - 6% W, and 60 - 85% Fe. The JP513VC powder mixture can also include up to 20% of pure iron, up to 3% of copper powder, additives such as MnS powder to enhance machinability, and die lubricants such as zinc stearate. For example, the mixture can include 50% of the first iron-based powder, 30% of the second iron-based powder, 17% of pure iron powder, 2% of copper powder, 0.5% of MnS powder, and 0.5% of die lubricant. VC carbide is likely to be the hardest among the common metal carbides used in the PM industry. It has a very high melting point (∼2810 °C) and chemical stability. Therefore, it can be one of the ideal metal carbide particles added to PM materials to improve the wear and corrosion resistance of the materials in the environment and at high temperatures. The vanadium carbide particles can be vanadium carbide (VC) and / or vanadium carbonitride (VCN) particles, which are present in an amount of 0.5 - 5 wt.% of the second iron-based powder and have an average particle size of 1 - 150 microns. Due to the high melting point of the vanadium carbide particles, they can be more evenly distributed in the powder mixture than the vanadium carbide precipitates formed from a tool steel composition containing carbon and vanadium, and have a more uniform particle size.

[0021] The first iron-based powder can be an atomized powder that has been annealed and preferably does not undergo significant phase transformation after sintering. However, the first iron-based powder will undergo some bainite phase transformation during the cooling period after sintering (e.g., sintering at 1120 °C), which starts from about 235 °C and is completed at about 165 °C, with a cooling rate between 1 °C / min and 6 °C / min. The second iron-based powder preferably undergoes a martensite phase transformation during the cooling period starting from the sintering process (e.g., sintering at 1120 °C), which starts from about 245 °C (Ms) and is completed at about -10 °C (Mf). Therefore, cryogenic treatment will be beneficial to the properties of JP513VCVC materials, such as dimensional stability, fatigue strength, and VSI retention ability.

[0022] During the sintering process, the JP513VC powder mixture can optionally be infiltrated with copper. Based on the principle of capillary force, the "thin" pores in the compacted powder are the preferred sites for the copper infiltration process. In one example, near-spherical or ellipsoidal powders can be used for the first iron-based powder, and the compacted powder can be infiltrated with about 13 wt.% of infiltrated copper. Thin gaps are formed between the powder particles after compaction, and copper infiltration can be beneficial to the performance of engine parts.

[0023] The JP513VC powder mixture can be used for hot forging applications. The concept of applying the powder metal forging process is to significantly increase the component density to near the theoretical value of 100%. Therefore, by using a ductile powder as the second iron-based powder and a powder not suitable for hot forging as the first iron-based powder, the mixture can be hot forged to the desired density. For the same consideration, the JP513VC powder mixture can be used for applying the metal injection molding (MIM) process.

[0024] During the compaction process, the first iron-based powder preferably does not deform significantly under the compaction force, while the second iron-based powder and the pure iron powder deform significantly, which allows for a good bond to form between the powders. The copper phase can undergo diffusion, which helps with the bond between the powders.

[0025] The shape of the MnS powder can vary depending on the location where the MnS powder is located. Containing 17 wt.% of pure iron powder, the iron powder can be fully bonded to all powder types present in the JP513VC mixture. A large amount of infiltrated copper can penetrate the gaps between the pure iron powders, which may be due to the higher capillary force between the pure iron particles. The fine particles in the second iron-based powder can be carbides rich in molybdenum and chromium. During the powder atomization process, the size and distribution of Mo- and Cr-rich carbides can be formed.

[0026] The apparent hardness of sintered JP513VC can be about HRc 49, which makes JP513VC suitable for heavy-duty intake and exhaust engine VSI applications. The friction properties of the material can be improved after the JP513VC powder mixture is treated with steam, especially in the case of no copper infiltration.

[0027] JP513VC sintered engine parts can be manufactured using conventional compaction and sintering processes. The JP513VC powder mixture concept preferably includes two iron-based powders, an iron binder powder, and an additive powder to enhance processability and the desired engineering application properties. The JP513VC powder includes a high-hardness first iron-based powder having a spherical and / or ellipsoidal shape, combined with a ductile and softer second iron-based powder to provide a high apparent density PM engineering part for high wear-resistant applications. The combination between the two iron-based powders, the iron binder powder, the solid lubricant powder, and the additive copper powder is preferably good, with a high sintering density (>7.5 g / cm 3 ). In addition, the mixing ability of JP513VC with the required powder characteristics and distribution can provide very uniform powder mixing conditions, enabling the achievement of the desired high material properties.

[0028] The softer second iron-based powder and the pure iron powder have irregular shapes. Therefore, both the second iron-based powder and the pure iron powder can deform during the compaction process, such that they surround the harder first iron-based powder.

[0029] Except for the vanadium carbide particles added to the second iron-based powder, no other hard particles / powders (such as additive silicides, intermetallic compounds, Mo-based, Co-based, and Fe-Mo hard particle powders) are added to the powder mixture. The harder first iron-based powder has a certain proportion of iron-rich intermetallic phases, Fe-Co solid solution phases, and bainite (with or without a small amount of martensite) structures, which provide significant wear resistance. After compaction and sintering, the harder first iron-based powder can be present in a high percentage with a uniform three-dimensional distribution, and the softer second iron-based powder and the solid solution-strengthened iron portion (after sintering) can provide a mixture with the toughness and improved wear resistance (e.g., reduced adhesive wear) required for engineering applications.

[0030] The harder first iron-based powder includes intermetallic sigma phases and carbides that remain in the microstructure at the sintering temperature. The diffusion of copper into the harder first iron-based powder is minimal, while the copper diffusing into the pure iron and the softer second iron-based powder may form ε-copper in the second iron-based powder, thereby inducing a precipitation hardening effect and having a solid solution strengthening effect on the pure iron as a solute.

[0031] In one embodiment, a powder mixture useful for manufacturing sintered engine parts, such as valve seat inserts, includes a first iron-based powder and a second iron-based powder, wherein the first iron-based powder has a higher hardness than the second iron-based powder. The first iron-based powder includes, by weight percentage, 1-2% Cr, 10-25% Cr, 5-20% Mo, 15-25% Co, and 30-60 wt.% Fe. The second iron-based particles include a vanadium-free tool steel powder, and the second iron-based powder further includes vanadium carbide particles in an amount sufficient to reduce adhesive wear. According to various options, (a) the first iron-based powder has a microstructure with an interdendritic and intra-dendritic solidification substructure, with up to 25% sigma phase; (b) the powder mixture further includes up to 20% Fe powder; (c) the powder mixture includes up to 3% Cu powder; (d) the powder mixture includes up to 2% MnS powder; (e) the powder mixture includes up to 2% die lubricant; (f) the first iron-based powder contains, consists essentially of, or consists of: 1-2% C, 10-25% Cr, 5-20% Mo, 15-25% Co, up to 1% Mn, up to 1% Si, up to 5% Ni, up to 5% W, up to 2% V, up to 0.5% B, up to 0.1% P, up to 0.1% S, up to 0.5% N, up to 0.5% Nb, with the balance being 30-60% Fe and incidental impurities; (g) the vanadium-free tool steel of the second iron-based powder contains, consists essentially of, or consists of: 1-1.5% C, 3-15% Cr, 5-7% Mo, 3-6% W, up to 1% Mn, up to 1% Si, with the balance being 60-85% Fe and incidental impurities, and optionally without Ni, optionally without Co, and optionally without Nb; (h) the first iron-based powder is present in an amount of 40-60 wt.% and the second iron-based powder is present in an amount of 20-40 wt.%; (i) the powder mixture includes Fe powder, Cu powder, and MnS powder, the first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, the Fe powder is present in an amount of 15-20 wt.%, the Cu powder is present in an amount of 1-3%, and the MnS powder is present in an amount of 0.1-1 wt.%; (j) the powder mixture does not contain additive silicides, Mo-based, Co-based, and intermetallic hard powder particles; (k) the first iron-based powder has a microstructure consisting of 40-60 vol.% interdendritic regions and 60-40 vol.% intra-dendritic regions; and / or (l) the powder mixture does not contain Co-based, Mo-based, or intermetallic hard particle powders with a hardness greater than that of the first iron-based powder.

[0032] The powder mixture can be used to manufacture sintered engine parts, such as valve seat inserts, where the powder mixture is compacted into the shape of the engine part and sintered to form a sintered powder mixture, optionally infiltrated with copper. According to various options, (a) the sintered powder mixture can have a density of at least 7.5 g / cm 3 ; (b) the first iron-based powder can have a microstructure consisting of 40 - 60 vol.% interdendritic regions and 60 - 40 vol.% intradendritic regions; (c) the sintered mixture can be free of hard particles having a hardness greater than the hardness of the first iron-based powder; (d) the sintered mixture can be free of silicides, Mo-based, Co-based or intermetallic hard particles; (e) the first iron-based powder can be present in an amount of 40 - 60 wt.%, the second iron-based powder can be present in an amount of 20 - 40 wt.%, and the Fe powder can be present in an amount of 15 - 20 wt.%; and / or (f) the first iron-based powder can be present in an amount of 40 - 60 wt.%, the second iron-based powder can be present in an amount of 20 - 40 wt.%, the Fe powder can be present in an amount of 15 - 20 wt.% and copper can be present in an amount of 10 - 15 wt.%.

[0033] A method of manufacturing a sintered engine part (such as a valve seat insert) can include forming a mixture by mixing a first iron-based powder with a second iron-based powder, compacting the mixture and sintering the mixture. According to various options, (a) sintering can include preheating the powder mixture at 560 °C, 850 °C and 950 °C for 5 - 20 minutes and then sintering at 1120 °C for 40 - 60 minutes; (b) sintering can include a pressing and sintering process; (c) cryogenic treatment of the sintered part in liquid nitrogen; (d) steam treatment of the sintered part; and / or (e) sintering can be carried out while infiltrating the mixture with copper. Examples

[0034] JP513VC can be made from a mixture of the following powders listed in Table 1, where the harder first iron-based powder is labeled "P1" and the softer second iron-based powder is labeled "P2":

[0035] Table 1

[0036]

[0037] The JP513VC powder metal part design preferably includes a mixture of a hard iron-based powder (P1) containing an intermetallic phase (including sigma phase) and a softer iron-based powder having a vanadium-free tool steel composition (including VC particles, pure iron, additive copper, solid lubricant and copper infiltration). The sintered part can be infiltrated with 13 wt.% or 18 wt.% of copper. In one example, the first and second iron-based powders can be mixed in a weight ratio of 1.67 (50 wt.% of the first iron-based powder to 30 wt.% of the second iron-based powder).

[0038] In this example, the powder mixture may include 50 wt.% of a first iron-based powder, 30 wt.% of a second iron-based powder, 0.5 wt.% of a lubricant, 0.5 wt.% of MnS, 17 wt.% of reduced iron powder, and 2 wt.% of an additive copper.

[0039] The part can be manufactured using standard sintering times, including preheating (48 minutes) at 560 °C, 850 °C, and 950 °C for 16 minutes each, and sintering at 1120 °C for 48 minutes. Cryogenic treatment can be carried out by soaking in liquid nitrogen for 15 minutes, followed by tempering at 538 °C for one hour.

[0040] A mixture of P1 (50 wt.%) and vanadium-free tool steel powder P2 (30 wt.%) can show very similar apparent densities. Copper penetrations of 13 wt.% and 18 wt.% should not affect the internal microstructure of the vanadium-free tool steel powder. Excess copper can form on the bottom surface with 18 wt.% copper penetration. However, the copper penetration can reach the required level of approximately 14.5 wt.%. The apparent density of the sample should be good, without large PM porosities. The P1 alloy powder can be evenly distributed in the mixture with P2, pure iron, and other additive powders. Spherical or oval P1 powders are very beneficial for the wear resistance of PM materials, with good bonding between P1 and P2 iron-based powders. From the surface to the center of the sintered part, the copper penetration should be sufficient, with the surface PM pores completely filled with copper.

[0041] The microhardness maps of all six JP513VC samples under a 500 g load show a good apparent microhardness distribution. Generally, the samples with 13 wt.% copper penetration show lower hardness under a 500 g load, which is likely related to the PM compaction density and PM pore density, and the PM pore density is not completely filled by copper penetration.

[0042] P1 powder can be considered a hardenable alloy because solid-phase phase transformation may occur, where only a small portion of the alloy undergoes solid-state phase transformation. In the hardened state (1700 °F), compared to the same alloy in the as-cast condition, P1 powder may have an increased interdendritic region and a reduced intra-dendritic region. The increase in the interdendritic region is achieved through the diffusion process between the interdendritic region and the intra-dendritic region at high temperatures (e.g., hardened at 1700 °F). It is estimated that approximately 25 vol.% of the interdendritic region is sigma phase, and approximately 25 vol.% of the intra-dendritic region is sigma phase. It is estimated that approximately 75 vol.% of high Cr high Mo ferrite exists in the interdendritic region, and approximately 75 vol.% of the γFe,αCo solid solution (fcc) phase exists in the intra-dendritic region.

[0043] Thus, P1 powder in the hardened or hardened + tempered state, having 50 vol.% interdendritic regions and 50 vol.% intergranular regions, may have a microstructure containing up to about 37.5 vol.% high Cr and Mo ferrite phase, up to about 37.5 vol.% γFe,αCo solid solution (fcc) phase, up to about 25.0 vol.% sigma phase, and the balance up to about 5.0 vol.% of a mixture of bainite, martensite, and carbide phases.

[0044] In one embodiment, sintered engine parts (e.g., valve seat inserts, valve guides, turbocharger components, bushings, friction pads, etc.) can be manufactured by preparing a powder mixture that is 40 - 60 wt.% of a first iron-based powder, 20 - 40 wt.% of a second iron-based powder, 15 - 25 wt.% of pure iron powder, optionally up to 5 wt.% of copper powder, optionally up to 5 wt.% of manganese sulfide, and optionally up to 5 wt.% of a die lubricant, by weight. The powder mixture can be compacted into a shape suitable for an engine part for an internal combustion engine and sintered (e.g., single press and sinter or double press and sinter) with or without copper infiltration. The sintered part can be cryogenically treated to alter the microstructure of the sintered part. During sintering, the iron powder can diffuse into the second iron-based powder, and / or elements such as Cu, Cr, and Mo from other powders can diffuse into the iron powder. In the second iron-based powder, in the case where the second iron-based powder contains vanadium, vanadium can combine with carbon during sintering and / or heat treatment of the sintered part to form vanadium carbide precipitates, and the vanadium carbide particles can be more uniformly distributed than the vanadium carbide precipitates, having a desired particle size.

[0045] In the sintered part, the first iron-based powder can contain sigma phase in the interdendritic regions and the intergranular regions. For example, up to 30 vol.% sigma phase (e.g., 20 - 30 vol.% sigma phase) can be present in the interdendritic regions, and up to 30 vol.% sigma phase (e.g., 20 - 20 vol.% sigma phase) can be present in the intergranular regions. By adding 40 - 60 wt.% of the first iron-based powder to the powder mixture, the sintered part can contain 8 - 18 vol.% sigma phase (e.g., 10 - 15 vol.% sigma phase).

[0046] In the sintered part, the first iron-based powder may include a face-centered cubic (FCC) solid solution phase of iron-cobalt (Fe-Co). For example, the intra-dendritic region may include 60-90 vol.% (e.g., 70-80 vol.%) of the Fe-Co solid solution phase. By adding 40-60 wt.% of the first iron-based powder to the powder mixture, the sintered part may contain 10-30 vol.% of the Fe-Co solid solution phase (e.g., 15-25 vol.% of Fe-Co solid solution).

[0047] In the sintered part, the first iron-based powder may include ferrite (e.g., high-chromium ferrite) in the inter-dendritic region. For example, up to 60-90 vol.% of ferrite (e.g., 70-80 vol.% of ferrite) may be present in the inter-dendritic region. By adding 40-60 wt.% of the first iron-based powder to the powder mixture, the sintered part may contain 10-30 vol.% of the high-chromium ferrite phase (e.g., 15-25 vol.% of high-chromium ferrite).

[0048] In the sintered part, the second iron-based powder may include 70-80 vol.% (e.g., about 75 vol.%) of tempered martensite and 20-30 vol.% (e.g., about 25 vol.%) of chromium-molybdenum carbide. By adding 20-40 wt.% of the second iron-based powder to the powder mixture, the sintered part may contain 10-30 vol.% of tempered martensite and 5-10 vol.% of chromium-molybdenum carbide.

[0049] For pure iron powder, an obvious element diffusion process occurs during the sintering process. Depending on the post-sintering treatment conditions, the pure iron powder may be composed of ferrite, bainite, martensite, or a combination thereof. In addition, the sintered part may be cryogenically treated with liquid nitrogen. In this case, more than 90 vol.% of the combined pure iron powder / second iron-based powder may be composed of the tempered martensite phase and up to 10 vol.% of ferrite, or bainite, or ferrite + bainite. In the sintered part, the pure iron powder may contain up to 10 vol.% of ferrite (or bainite, or bainite plus ferrite). Therefore, after adding 10-20 wt.% of pure iron powder to the powder mixture, the sintered part may contain 1-2% of ferrite, bainite, or ferrite plus bainite.

[0050] Sintered engine parts, such as VSI, can be heat-treated by hardening and tempering treatments to provide a tempered martensite microstructure. For example, the sintered and heat-treated engine parts (such as VSI) may include at least 25 vol.% (e.g., 30-40 vol.%) of tempered martensite.

[0051] In one example, sintered and heat-treated engine parts (such as VSI) may include 10 - 15 vol.% (e.g., 12 - 13 vol.%) of sigma phase, 30 - 40 vol.% (e.g., 34 - 36 vol.%) of martensite, 20 - 25 vol.% (e.g., 21 - 23 vol.%) of ferrite, up to 2 vol.% of bainite, 20 - 25 vol.% (e.g., 21 - 23 vol.%) of iron-cobalt solid solution phase, and 5 - 10 vol.% of high-chromium carbide.

[0052] In the above example, J120 is used as P2 powder. J120 includes, by weight%, 1.2 - 1.5% C, 0.3 - 0.6% Mn, 0.3 - 0.6% Si, 3.5 - 4.25% Cr, 6 - 7% Mo, 5 - 6% W, with the balance being Fe.

[0053] After sintering and heat treatment, JP513VC can have high compressive strength and ultimate tensile fracture strength at high temperatures, as Figure 1 and Figure 2 shown.

[0054] Figure 1 is a graph showing the relationship between the compressive yield strength of JP513VC and temperature, where the value of the compressive yield strength (CYS) is in ksi, as shown in Table 2 below.

[0055] Table 2 Temperature °F CYS (ksi) 75 199.3 200 194.2 400 194.3 600 186.5 800 173.8 900 163.3 1000 140.2 1100 97.7 1200 46.5

[0056] Figure 2 is a graph showing the relationship between the ultimate tensile fracture strength (UTS) of JP513VC and temperature, where the value of UTS is in ksi, as shown in Table 3 below.

[0057] Table 3 Temperature °F UTS (ksi) 75 94.6 400 79.6 800 66.7 900 68.3 1000 56.8 1200 32.2

[0058] As Figure 1 and Figure 2 shown by the figures in and the data in Table 2 and Table 3, JP513VC exhibits high CYS and UTS in the range from ambient temperature (75°F) to about 800°F.

[0059] The preferred embodiments are illustrative only and should not be considered restrictive in any way. The scope of the present invention is given by the appended claims, rather than the preceding description, and all variations and equivalents falling within the scope of the claims are intended to be included therein.

Claims

1. A powder mixture for making a sintered engine part, the powder mixture comprising a first iron-based powder and a second iron-based powder, wherein the first iron-based powder has a higher hardness than the second iron-based powder, the first iron-based powder comprising, by wt.%, 1-2% C, 10-25% Cr, 5-20% Mo, 15-25% Co and 30-60% Fe, the second iron-based powder comprising a vanadium-free tool steel powder, wherein the second iron-based powder further comprises vanadium carbide particles in an amount sufficient to reduce adhesive wear.

2. The powder mixture of claim 1, wherein (a) the first iron-based powder has a microstructure of inter-dendritic and intra-dendritic phases with up to 25 vol.% (volume percentage) of sigma phase, (b) the powder mixture further comprises, by wt.%, up to 20% Fe powder, up to 3% Cu powder, up to 2% MnS powder and up to 2% die lubricant, (c) the first iron-based powder comprises, consists essentially of, or consists of: (d) the vanadium-free tool steel of the second iron-based powder comprises, consists essentially of, or consists of, by wt.%, 1-1.5% C, 3-15% Cr, 5-7% Mo, 3-6% W, up to 1% Mn, up to 1% Si, the balance being 60-85% Fe and incidental impurities, and optionally free of Ni, optionally free of Co, and optionally free of Nb.

3. The powder mixture of claim 1, wherein the first iron-based powder is present in an amount of 40-60 wt.%, and the second iron-based powder is present in an amount of 20-40 wt.%.

4. The powder mixture of claim 1, wherein the vanadium carbide particles have an average particle size of 1 to 150 microns.

5. The powder mixture of claim 1, wherein the vanadium carbide particles are vanadium carbonitride particles having an average particle size of 1 to 150 microns.

6. The powder mixture of claim 1, wherein the vanadium carbide particles are present in an amount of 0.5 to 5 wt. % of the second iron-based powder.

7. The powder mixture according to claim 1, wherein the powder mixture comprises Fe powder, Cu powder and MnS powder, the first iron-based powder is present in an amount of 40-60wt.%, the second iron-based powder is present in an amount of 20-40wt.%, the Fe powder is present in an amount of 15-20wt.%, the Cu powder is present in an amount of 1-3%, and the MnS powder is present in an amount of 0.1-1wt.%.

8. The powder mixture of claim 1, wherein, in addition to the vanadium carbide particles, the powder mixture is free of additive silicides and intermetallic hard powder particles.

9. The powder mixture of claim 1, wherein the first iron-based powder has a microstructure consisting of 40-60 vol.% of interdendritic region and 60-40 vol.% of intradendritic region.

10. The powder mixture of claim 1, wherein the powder mixture does not contain Co-based and / or Mo-based particle powders having a hardness greater than that of the first iron-based powder, except for the vanadium carbide particles.

11. A sintered engine part comprising the powder mix of claim 1, wherein the powder mix has been compacted into the shape of an engine part and sintered to form a sintered powder mix optionally infiltrated with copper.

12. The sintered engine part according to claim 11, wherein the sintered powder mixture has a particle size of at least 7.5 g / cm 3 density.

13. The sintered engine part of claim 11, wherein the first iron-based powder has a microstructure consisting of 40-60 vol.% inter-dendritic region and 60-40 vol.% intra-dendritic region.

14. The sintered engine part according to claim 11, wherein: In addition to the vanadium carbide particles, the sintered mixture does not contain silicide particle powder or intermetallic hard particle powder having a hardness greater than that of the first iron-based powder.

15. The sintered engine part according to claim 11, wherein the sintered mixture does not contain additive silicide particle powder, Mo-based particle powder, Co-based particle powder or intermetallic hard particle powder.

16. The sintered engine part of claim 11, wherein the first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, and Fe powder is present in an amount of 15-20 wt.%.

17. The sintered engine part of claim 11, wherein the first iron-based powder is present in an amount of 40-60 wt.%, the second iron-based powder is present in an amount of 20-40 wt.%, Fe powder is present in an amount of 15-20 wt.%, and copper is present in an amount of 10-15 wt.%.

18. A method of manufacturing the sintered engine part of claim 11, the method comprising forming a mixture by mixing the first iron-based powder with the second iron-based powder, compacting the mixture, and sintering the mixture.

19. The method of claim 18, wherein the sintering comprises preheating the powder mixture at 560°C, 850°C and 950°C for 16 minutes and then sintering at 1120°C for 48 minutes.

20. The method of claim 18, wherein (a) the sintering comprises a pressing and sintering process; (b) the method further comprises cryogenically treating the sintered engine part in liquid nitrogen; (c) the method further comprises steam treating the sintered engine part; and / or (e) the sintering is performed while the mixture is infiltrated with copper.